Arterial Calcification Due to Deficiency of CD73 (ACDC) As One of Rheumatic Diseases Associated With Periarticular Calcification. Issue 4 (June 2015) - Ichikawa, Naomi; Taniguchi, Atsuo; Kaneko, Hirotaka; Kawamoto, Manabu; Sekita, Chieko; Nakajima, Ayako; Yamanaka, Hisashi
Abstract : Abstract: In 2011, St Hilaire et al ( N Engl J Med . 2011;364:432–442) identified mutations in the ecto-5′-nucleotidase ( NT5E ) gene, which encodes CD73, in members of 3 families with symptomatic arterial and joint calcifications. The deficiency of CD73 involves the extracellular adenosine metabolism that influences inorganic pyrophosphate and phosphate metabolism and leads to tissue calcification. Herein, we report an additional case with arterial calcification due to deficiency of CD73. Genetic analyses revealed that the patient was a compound heterozygote of mutations in the NT5E gene. The present case had intermittent monoarthritis of the finger joints and early-onset osteoarthritis in the hands. Occlusion of calcified peripheral arteries is the most important outcome of the disease. However, the rheumatic manifestations may be important clues to the diagnosis. Rheumatologists should recognize deficiency of CD73 as a rheumatic disease.